John invested the money at simple interest for 4.22 years.
We have,
Invested amount = $ 4500
Rate of interest = 5.5 %
Time = t years
Maturity value = $ 5545
So,
Total interest earned = $ 5545 - $ 4500 = $ 1045
And,
Simple interest = (Principal × Rate × Time ) / 100
So, Using the mentioned formula,
1045 = ( 4500 × 5.5 × t ) /100
1045 = 45 × 5.5 × t
⇒
t = (1045) / (45 × 5.5)
⇒ t = 4.22 years
Therefore, John invested the money at simple interest for 4.22 years.
Learn more about simple interest here:
brainly.com/question/22621039
#SPJ10
Answer:
No Jeremy can not find the cost of the sneakers by adding the percents, you have to the math one sale discount at a time.
The answer is $45.90.
Step-by-step explanation:
You have to multiply $60 by 15%, getting $9. Subtract 9 from 60 and get the first discount price: $51. Then you will multiply 51 by `10% and get 5.1, subtract 5.1 from 51 and get your final sale price $45.90. If you added the percents together you would get an incorrect value of $45. Close but not the correct answer.
Answer:
169, 196, 225
Step-by-step explanation:
13*13=169
14*14=196
15*15=225
Can I get brainliest!
Answer:
since, v=a(square) ×h
Step-by-step explanation:
v=a(squate)cm×hcm
v=25(square)cm×6cm
v=625cm×6ccm
v=3,750cm(cube)
<u>vertex</u>
y = 3(x - 2)² - 4
y = 3((x - 2)(x - 2)) - 4
y = 3(x² - 2x - 2x + 4) - 4
y = 3(x² - 4x + 4) - 4
y = 3(x²) - 3(4x) + 3(4) - 4
y = 3x² - 12x + 12 - 4
y = 3x² - 12x + 8
3x² - 12x + 8 = 0
x = <u>-(-12) +/- √((-12)² - 4(3)(8))</u>
2(3)
x = <u>12 +/- √(144 - 96)</u>
6
x = <u>12 +/- √(48)
</u> <u> </u> 6<u>
</u>x =<u> 12 +/- 6.93</u>
<u /> 6
x = 2 +/- 1.155
x = 2 + 1.155 x = 2 - 1.155
x = 3.155 x = 0.845
y = 3x² - 12x + 8
y = 3(3.155)² - 12(3.155) + 8
y = 3(1.334025) - 3.786 + 8
y = 4.002075 - 3.786 + 8
y = 0.216075 + 8
y = 8.216075
(x, y) = (3.155, 8.216075)
or
y = 3x² - 12x + 8
y = 3(0.845)² - 12(0.845) + 8
y = 3(0.714025) - 10.14 + 8
y = 2.142075 - 10.14 + 8
y = -7.857925 + 8
y = 0.142675
(x, y) = (0.845, 0.142675)
<u>y-intercept</u>
y = 3x² - 12x + 8
y = 3(0)² - 12(0) + 8
y = 3(0) - 0 + 8
y = 0 - 0 + 8
y = 0 + 8
0 = -y + 8
y = 8
(x, y) = (0, 8)
-------------------------------------------------------------------------------------------
<u>vertex</u>
y = 4(x - 5)² = 1
y = 4(x - 5)² - 1
y = 4((x - 5)(x - 5)) - 1
y = 4(x² - 5x - 5x + 25) - 1
y = 4(x² - 10x + 25) - 1
y = 4(x²) - 4(10x) + 4(25) - 1
y = 4x² - 40x + 100 - 1
y = 4x² - 40x + 99
4x² - 40x + 99 = 0
x = <u>-(-40) +/- √((-40)² - 4(4)(99))</u>
2(4)
x = <u>40 +/- √(1600 - 1584)</u>
8
x = <u>40 +/- √(16)</u>
8
x = <u>40 +/- 4</u>
8
x = 5 +/- 1/2
x = 5 + 1/2 x = 5 - 1/2
x = 5 1/2 x = 4 1/2
y = 4x² - 40x + 99
y = 4(5 1/2)² - 40(5 1/2) + 99
y = 4(30 1/4) - 220 + 99
y = 121 - 220 + 99
y = -99 + 99
y = 0
(x, y) = (5 1/2, 0)
or
y = 4x² - 40x + 99
y = 4(4 1/2)² - 40(4 1/2) + 99
y = 4(20 1/4) - 180 + 99
y = 81 - 180 + 99
y = -99 + 99
y = 0
(x, y) = (4 1/2, 0)
<u>y-intercept</u>
y = 4x² - 40x + 99
y = 4(0)² - 40(0) + 99
y = 4(0) - 0 + 99
y = 0 - 0 + 99
y = 0 + 99
y = 99
(x, y) = (0, 99)
--------------------------------------------------------------------------------------------
<u>vertex</u>
y = (x - 1)² = 2
y = (x - 1)² - 2
y = ((x - 1)(x - 1)) - 2
y = (x² - x - x + 1) - 2
y = x² - 2x + 1 - 2
y = x² - 2x - 1
x² - 2x - 1 = 0
x = <u>-(-2) +/- √((-2)² - 4(1)(-1))</u>
2(1)
x = <u>2 +/- √(4 + 4)</u>
2
x = <u>2 +/- √(8)</u>
2
x = <u>2 +/- 2.83</u>
2
x = 1 +/- 1.415
x = 1 + 1.415 x = 1 - 1.415
x = 2.415 x = 0.415
y = x² - 2x - 1
y = (2.145)² - 2(2.145) - 1
y = 4.60125 - 4.029 - 1
y = 0.57225 - 1
y = 0.42775
(x, y) = (2.415, 0.42775)
or
y = x² - 2x - 1
y = (0.415)² - 2(0.415) - 1
y = 0.172225 - 0.83 - 1
y = -0.657775 - 1
y = -1.657775
(x, y) = (0.415, -1.657775)
<u>y-intercept</u>
y = x² - 2x - 1
y = (0)² - 2(0) - 1
y = 0 - 0 - 1
y = 0 - 1
y = -1
(x, y) = (0, -1)